An analysis of personal loans at a local bank revealed the following facts: 10% of all personal loans are in default (D), 90% of all personal loans are not in default (D´), 20% of those in default are
what are the steps to solving this WITHOUT using Lhopitals rule?-You can use the limits tanx/x = 1 and sinx/x = 1
lim (x-->0) tan(4x)/sin(6x)
= lim (x-->0) (6x/6x)(4x/4x)(tan(4x)/sin(6x))
= lim (x-
what are the steps to solving this WITHOUT using Lhopitals rule?-You can use the limits tanx/x = 1 and sinx/x = 1
lim (x-->0) tan(4x)/sin(6x)
= lim (x-->0) (6x/6x)(4x/4x)(tan(4x)/sin(6x))
= lim (x-
P(the sum is multiple of 4 or greater than 9)
The answer is 7/18, but I dont understand how you get it. Please explain step by step. THANK YOU!-hi deer, (sorry, cow !)
just list in a table: favorable
Im soo brain dead right now and reallly need help figuring out how to solve these problems. Im not looking for answers, just the steps so I can understand what to do! ANy help at all would be so appre
Can anyone tell me how you get from step A to B?
A)(5/3)^k+(5/3)^k-1
B)((5/3)^k-1) x ((5/3)+1)
I just dont understand what steps to take to get from A to B.It goes from addition to multiplication, th
p3(x) for e^(3x) about x=-1-e^x about x = 0:
e^x = 1 + x + x²/2! + x³/3! + ....
e^(3x) about x = 0
e^(3x) = 1 + 3x + (3x)²/2! + (3x)³/3! + ....
e^(3x) about x = -1
=> e^(3(x+1)) about x = 0
e^(3(x+1
I would think this is true, but I am not positive.Does anyone have a counter example showing i is false?-of course its true -- use the chain rule
d(f^2) = 2 f df
since f is differentiable, df exists
Any help you can offer, I will greatly appreciate. Thank you!
4. Give an example that shows that not all linear equations can be rewritten in the slope-intercept form of y=mx+b
6. Find an equation f
A manufacturer of lighting fixtures has daily production costs of C = 800 − 30x + 0.25x^2, where C is the total cost (in dollars) and x is the number of units produced. How many fixtures should be pro
Simplify: 4(3x-1)-3(2x+3)
Answer question please:
Use the formula s=6r2 (2 is exponent) + 6h to find s if r= 2 and h=4-In order to simplify4(3x-1)-3(2x+3) you would use FOIL (First Outer Inner Last).
Since i to the fourth power equals 1, isnt the fourth root of 1 i? Thanks for your help!-i^1 = sqrt(-1)
i^2 = -1
i^3 = -i or -sqrt(-1)
i^4 = 1
you have a nice idea, but unfortunately that is not the
Collect all terms in one side,
x^2 + x - 2 = (x+2)(x-1) = 0
x = -2, 1-2 - x^2 = x
-x^2 - x + 2 = 0 (Multiply by -1)
x^2 + x - 2 = 0 (Factor this or use quadratic formula.)
(x+2)(x-1)=0
x = -2 or x =